2019
DOI: 10.1016/j.jaccas.2019.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Correction of a Malpositioned Portico Transcatheter Aortic Valve Using a Snare Maneuver

Abstract: A 75-year-old woman with severe aortic stenosis underwent transcatheter aortic valve replacement using a 23-mm self-expanding Portico valve (Abbott). After complete deployment, it was found to be unacceptably low, with significant paravalvular regurgitation. The valve was pulled upward to the correct position successfully by using the snare maneuver. ( Level of Difficulty: Advanced. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This technique, despite being recognized to manage several complications after TAVI, 10 is mainly used to valve repositioning after low implantation, in cases of severe paravalvular regurgitation, or to facilitate valve implantation in challenging anatomies. 13 , 14 Its use for valve retrieval after coronary occlusion is seldomly reported in medical literature, and to best of our knowledge, this is one the first case reports describing it to resolve a life-threatening coronary occlusion after TAVI.…”
Section: Discussionmentioning
confidence: 92%
“…This technique, despite being recognized to manage several complications after TAVI, 10 is mainly used to valve repositioning after low implantation, in cases of severe paravalvular regurgitation, or to facilitate valve implantation in challenging anatomies. 13 , 14 Its use for valve retrieval after coronary occlusion is seldomly reported in medical literature, and to best of our knowledge, this is one the first case reports describing it to resolve a life-threatening coronary occlusion after TAVI.…”
Section: Discussionmentioning
confidence: 92%
“…There have been several case reports of snaring maneuvers described in the literature. Ponangi et al reported [7] a successful use of a single snare technique for a downward dislocated Portico valve with a 25-mm Amplatzer Gooseneck Snare. However, there were no significant calcifications of the aorta present which could aggravate the repositioning procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In all previous cases the single snare technique was described as technically demanding but feasible. A technique with two snares with additional right radial access has also been proposed but not used [7]. Failure of the single snare technique in our complex case of Portico valve dislocation in the LVOT led us to use a novel, double snaring technique with two snares.…”
Section: Discussionmentioning
confidence: 99%
“…4 To the best of our knowledge, there are very few cases in the literature like this case. 5 Th e case presented in this paper is one of them to only use a snare to reposition the Portico self-expanding bioprosthesis. In our case, we only used the snare technique to pull back the malpositioned prosthesis without using the balloon pull technique and without implantation of the second valve.…”
Section: Case Studymentioning
confidence: 99%